2022
DOI: 10.3390/f13091387
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical Composition, Crystallizability, and Microstructure of Decayed Wood-Fiber-Mat-Reinforced Composite Treated with Copper Triazole Preservative

Abstract: Wood-fiber-mat-reinforced composites (WFMRCs) possess excellent physical and mechanical properties and provide high structural performance, making them a suitable engineering structural material. However, WFMRCs are susceptible to biological attack by fungi and insects when they are used in outdoor environments. In this study, the efficacy of copper triazole (CuAz) preservative treatment in protecting WFMRC against decay by white- and brown-rot fungi (Trametes versicolor and Gloeophyllum trabeum, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Chemical treatment is one of the most common protections to reduce wood deterioration. Studies have shown that wood has good resistance to biological decay after proper preservative treatment [5][6][7]. Generally, it is desirable to achieve a significant degree of penetration in order to provide long-term durability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical treatment is one of the most common protections to reduce wood deterioration. Studies have shown that wood has good resistance to biological decay after proper preservative treatment [5][6][7]. Generally, it is desirable to achieve a significant degree of penetration in order to provide long-term durability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, wood has been used as the base material for the manufacture of these structures [9]. As a result, it is common to find hives made of carefully cut and planed dry wood [10,11]. However, from environmental and economic perspectives, wood is a resource that is not sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…However, from environmental and economic perspectives, wood is a resource that is not sustainable. This is due to its low durability and the accelerated degradation of the wood, which is caused by environmental conditions and the attack of pathogens [11,12].…”
Section: Introductionmentioning
confidence: 99%